أثر الثقافة التنظيمية على الأداء الوظيفي للعاملين "دراسة حالة مشفى الشهيد مازن إبراهيم في محافظة طرطوس" - برهوم, أديب; الشيخ حسن, فداء; سعيد, رشا (Latakia University Journal - Economic and Legal Sciences Series, 2018)
تلعب الثقافة التنظيمية دوراً مهماً في التأثير على سلوك العاملين في المنظمات، حيث هدفت هذه الدراسة إلى التعرف على أثر عناصر الثقافة التنظيمية (القيم التنظيمية, الاتجاهات التنظيمية, التوقعات التنظيمية) على الأداء الوظيفي للعاملين في مشفى الشهيد مازن إبراهيم في محافظة طرطوس. وتم جمع البيانات الأولية للبحث من خلال استبيان تم توزيعه على عينة عشوائية بسيطة من مجتمع البحث, وتم تحليل هذه البيانات من خلال برنامج الـ SPSS الإحصائي. ولاختبار فرضيات الدراسة فقد تم استخدم تحليل الانحدار المتعدد. ومن أهم النتائج التي تم التوصل إليها: 1- هناك مستويات جيدة لجميع عناصر الثقافة التنظيمية من وجهة نظر العاملين في مشفى الشهيد مازن إبراهيم في محافظة طرطوس. 2- لدى العاملين وجهات نظر محايدة تجاه الأداء الوظيفي في المشفى محل الدراسة. 3- وجود علاقة ارتباط بين عناصر الثقافة التنظيمية والأداء الوظيفي للعاملين. 4- وجود تأثير معنوي للقيم التنظيمية والاتجاهات التنظيمية والتوقعات التنظيمية على الأداء الوظيفي للعاملين. 5- كانت القيم التنظيمية أكثر الأبعاد تأثيراً على الأداء الوظيفي للعاملين في المشفى محل الدراسة, يليه على التوالي التوقعات التنظيمية, ثم الاتجاهات التنظيمية. Organizational culture plays an important role in influencing the behavior of employees in organizations, and this study aimed to identify the impact of the of the organizational culture elements (organizational values, organizational attitudes, organizational expectations) on the job performance of employees at the martyr Mazen Ibrahim's Hospital in Tartous Conservatism. Research primary information were collected through a questionnaire was distributed to a simple random sample of research community, the data were analyzed by the SPSS statistical program. The multiple regression was used to test the research hypotheses. The main findings of the study are: 1- There are good levels for all of the organizational culture elements from the employees' viewpoint at the martyr Mazen Ibrahim's Hospital in Tartous Conservatism. 2- The employees have neutral points of view for the job performance at the hospital under study. 3- There is a correlation relationship between organizational culture elements and job performance of employees. 4- There is a significant impact of the organizational values, organizational Expectations and organizational attitudes on the job performance of employees. 5- The organizational values had the most influental dimensions on the job performance of the employees at the hospital under study, then comes the organizational expectations, after that the organizational attitudes.